Croatian Public Procurement Law – Harmonisation with the EU - Boris Ljubanović; Bosiljka Britvić-Vetma (Zbornik Radova Pravnog Fakulteta u Splitu, 2011)
The authors of this paper discuss the issues of Croatian public procurement law and its harmonisation with EU law. The acquis communautaire of the EU dealing with public procurement is analysed within a so called primary legislative frameworjk and also in so called secondary legislative framework. The practice of the European Court is presented as are European Commission decisions. Also analysed is Croatian public procurement law and uits achievements in adopting the acquis communautaire of teh EU.